Ingredients of Family Cohesion, and its Implications for Community Cohesion: A Sociological Vision - Alkarbi, Shaikha; Abouelkheir, Omaima (Al-Adab Journal, 2023)
This study aims to identify the ingredients of family cohesion, to reveal of the relationship between the ingredients of family cohesion and its implications for community cohesion, and to reach recommendations that contribute to activating family cohesion and the reality of community cohesion. The study sought the answer to key question: What are the ingredients of family cohesion and their implications for community cohesion?The study worked on the sociological analytical method; in studying the ingredients of family cohesion and its implications for the community cohesion, through a critical presentation of the research heritage on family cohesion and community cohesion as an analytical attempt to some previous studies related to the subject of the research. To provide a scientific study on the impact of these ingredients; This is to reach scientific results and recommendations that show the importance of family cohesion in achieving community cohesion.The study concluded that family cohesion is an important part of the great interest in community cohesion, and great foundations are built on it in bringing about the required community development, which necessitates the need to pay attention to the family, and the family cohesion index, in the community construction. The study also found that the ingredients of family cohesion are important and multiple (structural, psychological, economic, health and religious), and all of them must be taken into consideration, to achieve family cohesion that produces a good family that respects each other’s members and is effective in community development. and sustainable required. At the level of community cohesion, the study showed that the ingredients of family cohesion have great repercussions on societal cohesion, as they are directly proportional to achieving them (as a percentage), meaning that the stronger the ingredients of family cohesion, the greater the community cohesion.The study recommended; The need to pay attention to family cohesion and community cohesion, and to develop many programs aimed at strengthening and raising awareness of these aspects, in addition to increasing the studies and scientific research in this area.